Evaluation of mortar with waste crushing composition for rural construction (Revista de Ciências Agroveterinárias, 2014)
The exploitation of mineral reserves in order to produce aggregate for making mortar and concrete has mortar has seen high growth in the northeast of the country, especially in Paraiba state. However, this operation entails the production of waste from the process of crushing rocks to reach the fraction of aggregate trade, known as tailings, thus polluting the environment. This work aimed to evaluate the compressive strength of mortars containing different amounts of tailings instead of natural sand for rural construction. The procedures according to NBR NM 248 (selection and classification of the tailings) and the NBR 13279 (determination of the uniaxial compressive strength) were performed. The results showed that the highest strength for the mortars with higher level of tailings and water/cement ratio was obtained by using 22 MPa for water/cement ration equal 0.65 and 100% replacement content of sand by tailings.
Keywords: Waste crushing; Mortar; Sand.